2014
DOI: 10.1007/978-3-319-12111-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Through-Life Engineering Services: The NedTrain Case

Abstract: Investing in all operational management aspects is of great importance to the proper management and maintenance of capital assets. The primary maintenance processes are to be up to the task and to have the organization of the production plants, statements of work, planning and work preparation well in order. Continuous improvement presupposes an atmosphere where presenting improvement proposals, reporting, and removing unsafe working conditions is encouraged as a matter of course. By conducting the technical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…The context of the case is a company that maintains passenger service rolling stock: NedTrain. van Dongen [48] gives insights about the maintenance strategy of NedTrain; Parada Puig et al [32] give more detail about its maintenance operations. This section is structured as follows.…”
Section: Results Of Case Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The context of the case is a company that maintains passenger service rolling stock: NedTrain. van Dongen [48] gives insights about the maintenance strategy of NedTrain; Parada Puig et al [32] give more detail about its maintenance operations. This section is structured as follows.…”
Section: Results Of Case Researchmentioning
confidence: 99%
“…It contains, for example, information on asset configuration, the maintenance program, technical KPIs, obsolescence management and technology refreshment plans. van Dongen [48] offers more detail. After (commissioning) fielding the new train series, the individual life cycle plan is coupled to the life cycle plan of the entire fleet.…”
Section: New Approach To Planning Maintenance During Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the railway sector the most commonly cited application of TES is the maintenance of locomotives and rolling stock. Particular examples include the application of real time monitoring to enable dynamic maintenance scheduling at NedTrain [115], the use of robots in automated train maintenance beyond simple inspection [61] and the extension of the life of London underground trains in the most cost effective manner [85] [116]. From the railway system's perspective various papers citing the work to improve the performance monitoring and measurement systems by utilising data [86] as well as the development of a model to improve the data gathering for more effective initial spare part assortment decision making based on a case study at Netherlands Train [112], offer examples of the future opportunities and challenges.…”
Section: Applications Of Through-life Engineering Servicesmentioning
confidence: 99%
“…The consideration and focus relative to data filters, computational and simulation models in support of TES design and application is well served within the literature and cover numerous aspects and applications. Nonaka et al [37] [146] [147] [146] remain significant contributors reporting on models in support of service and availability for use of machine tools whilst Toossi et al [86], van Dongen [115], Norris [85], Lingegard and Lindahl [117] offer models and the case for their application in the Rail Sectors of the UK, Sweden, and the Netherlands. Upon review it is observed that contributions relating to the generating of models within TES include the calculation of remaining useful life and MRO decisions [148] [149] [150], logistics [151], cost [67] [66] [108], obsolescence [152] [109] [153] and Inventory [151] [154] and all such contributions feature significantly.…”
Section: Features In the Effective Design Of Through-life Engineering...mentioning
confidence: 99%